Greek -ων Nouns between Indo-European heritage and language-specific innovations (Atti del Sodalizio Glottologico Milanese, 2019)
In this paper, Ancient Greek -ων nouns are analysed from the point of view of their word formation patterns. Seven patterns are individuated and their main features are presented and discussed. It is then noted that in the diachronic development of this noun class in Greek a tendency can be observed towards the creation of two synchronically coherent series of morphological features: oxytone accentuation is associated with feminine gender, maintenance of suffixal ablaut and deverbal derivation, whereas barytone accentuation is associated with masculine gender, levelling of suffixal ablaut and denominal/deadjectival derivation. KEYWORDS: morphology, Greek, word-formation, Indo-European, noun classes